Rheological and mechanical performance of asphalt binders and mixtures incorporating CaCO3 and LLDPE - Mohd Hasan, Mohd Rosli; You, Zhanping; Mohd Satar, Mohd Khairul Idham; Mohd Warid, Muhammad Naqiuddin; Mohd Kamaruddin, Nurul Hidayah; Poovaneshvaran, Sharvin (Scientific Research Publishing, 2019)
This study was conducted to assess the performance of modified asphalt binders and engineering properties of mixtures prepared with incorporation 3 vol% and 6 vol% of calcium carbonate (CaCO3), linear low-density polyethylene (LLDPE), and combinations of CaCO3 and LLDPE. The rheological properties of control and modified asphalt binders were evaluated using a series of testing such as rotational viscometer (RV), multiple stress creep recovery (MSCR) and bending beam rheometer (BBR) tests. Meanwhile, four-point beam fatigue test, the dynamic modulus (E*) test and tensile strength ratio (TSR) test were conducted to assess the engineering properties of asphalt mixtures. Based on the findings, the RV and MSCR test result shows that all modified asphalt binders have improved performance in comparison to the neat asphalt binders in terms of higher viscosity and improved permanent deformation resistance. A higher amount of CaCO3 and LLDPE have led modified asphalt binders to better recovery percentage, except the asphalt binders modified using a combination of CaCO3 and LLDPE. However, the inclusion of LLDPE into asphalt binder has lowered the thermal cracking resistance. The incorporation of CaCO3 in asphalt mixtures was found beneficial, especially in improving the ability to resist fatigue cracking of asphalt mixture. In contrast, asphalt mixtures show better moisture sensitivity through the addition of LLDPE. The addition of LLDPE has significantly enhanced the indirect tensile strength values and tensile strength ratio of asphalt mixtures.